Patterns of vertical geochemical zonality of groundwater in Donbass - A. I. Gavrishin (Известия высших учебных заведений: Геология и разведка, 2016)
The classification procedure referred to as the G-mode was applied to isolate hydrogeochemical homogeneous taxons in space and to compare them. Two geochemical tendencies were found in forming of groundwater chemical composition of the Donbass region: of direct and reverse hydrogeochemical zoning (for groundwater in Carbon, Cretaceous, Paleogene and Neogene deposits). The groundwater chemical composition changes from HCO3 - Ca2+ low salinity to Cl-- Na+ high salinity at the first tendency and to HCO3 - Cl-- Na+ low mineralized soda water to the second tendency. The origin of the soda-water is related to the processes of evaporation and condensation of water from out of CH-rich gas phase.